2016
DOI: 10.4268/cjcmm20161814
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of total flavones of Epimedium on oxidative stress induced by myocardial ischemia/reperfusion injury in rats

Abstract: To investigate the effects and mechanisms of total flavones of Epimedium (TFE) on oxidative stress induced by myocardial ischemia/reperfusion injury in rats, forty male SD rats were randomly divided into sham operated group, model group, diltiazem group and flavonoids of Epimedium low and high doses groups with 8 rats in each. Myocardial ischemia/reperfusion injury model was induced by ligaturing the left anterior descending artery for 30 min followed reperfusion for 4 h after TFE was taken by intragastric adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Modern studies found that HZ is rich in pharmacologically active substances, primarily avonoids and volatile components [6][7][8][9]. Pharmacological studies have demonstrated signi cant effects of avonoids and volatile components on myocardial ischemia injury in TCM [10][11][12][13]. HZ is used to treat vasculitis in modern clinical applications [14].…”
Section: Introductionmentioning
confidence: 99%
“…Modern studies found that HZ is rich in pharmacologically active substances, primarily avonoids and volatile components [6][7][8][9]. Pharmacological studies have demonstrated signi cant effects of avonoids and volatile components on myocardial ischemia injury in TCM [10][11][12][13]. HZ is used to treat vasculitis in modern clinical applications [14].…”
Section: Introductionmentioning
confidence: 99%